h - Hodler, J.; Zollikofer, Ch. L.; Schulthess, G. K.; SpringerLink (Online service) (Milano : Springer Milan, 2010)
This book deals with imaging of the abdomen and pelvis.During the last few years, there have been considerable advances in this subject, driven by clinical as well as technological developments. The authors,internationally renowned experts in their field,have contributed chapters that are disease-oriented and cover all relevant imaging modalities, including magnetic resonance imaging, computed tomography, and positron emission tomography, as well as image-guided interventions. As a result, this book offers a comprehensive review of the stateof- the art in imaging of the abdomen and pelvis. It is particularly relevant for general radiologists, radiology residents, interventional radiologists, and other clinicians wishing to update their knowledge in this discipline.
Workshops -- Emergency Radiology of the Abdomen: The Acute Abdomen -- Trauma of the Abdomen and Pelvis -- Diseases of the Esophagus and Stomach -- Small-Bowel Imaging: Pitfalls in Computed Tomography Enterography/Enteroclysis -- Diseases of the Small Bowel, Including the Duodenum $1 (BMRI -- Imaging of the Colon and Rectum: Inflammatory and Infectious Diseases -- CT Colonography: Updated -- Imaging of Diffuse and Inflammatory Liver Diseases -- Focal Liver Lesions -- Imaging Diseases of the Gallbladder and Bile Ducts -- Diseases of the Pancreas, I: Pancreatitis -- Diseases of the Pancreas, II: Tumors -- Adrenal Imaging and Intervention -- Renal Tumors -- Urinary Tract Obstruction and Infection -- Benign Diseases of the Female Genital Tract -- Malignant Diseases of the Female Genital Tract -- Magnetic Resonance Imaging of Prostate Cancer -- Imaging of the Male Pelvis: The Scrotum -- Spread of Metastatic Disease in the Abdomen and Pelvis -- Abdominal Vascular Disease: Diagnosis and Therapy -- Non-vascular Abdominal Disease: Diagnosis and Therapy -- An Approach to Imaging the Acute Abdomen in the Pediatric Population -- Imaging Uronephropathies in Children -- Integrated Imaging in Genitourinary Oncology: PET/CT Imaging -- Integrated Imaging in Gastrointestinal Oncology: PET/CT Imaging -- Nuclear Medicine Satellite Course (3z(BDiamond(3y (B-- Lymphoma: Diagnostic and Therapeutic Applications of Radiopharmaceuticals -- Conventional Nuclear Medicine in the Evaluation of Gastrointestinal and Genitourinary Tract Disorders -- PET in Hepatobiliary-Pancreatic Tumors -- PET in Tumors of the Digestive Tract -- Tumors of the Adrenergic System: Imaging and Therapy -- Neuroendocrine Tumors of the Abdomen: Imaging and Therapy -- Pediatric Satellite Course (3z(BKangaroo(3y (B-- Imaging Cystic Kidneys in Children -- Understanding Duplication Anomalies of the Kidney -- Malrotation: Techniques, Spectrum of Appearances, Pitfalls, and Management -- Pediatric Intestinal Ultrasonography.s
Keywords: Medicine; Radiology, Medical; Interventional radiology; Medicine & Public Health; Medicine/Public Health, general; Medicine/Public Health, general; Diagnostic Radiology; Interventional Radiology